IDENTIFIKASI POTENSI BAHAYA DENGAN PENDEKATAN JOB SAFETY ANALYSIS PADA BAGIAN PENGOLAHAN CRUMB RUBBER DI PT PERKEBUNAN NUSANTARA III (PERSERO) KEBUN GUNUNG PARA TAHUN 2014 - Mareza Wardani Nababan (Lingkungan dan Kesehatan Kerja, 2014)
In this modern human era, there are so many people that use elastic tools like rubber. The processing of rubber has many potential hazards, both from the engine and the environment in which it worked. The potential hazards that identified in the workplace is the first step in preventing work accidents. PT Perkebunan Nusantara III (Persero) Kebun Gunung Para is a state-owned company engaged in the business of rubber plantations, oil palm and rubber "ribbed smoked sheet" and "crumb rubber" processing factory. The company's data shows that the potential physical hazards are dominating work accidents in the factory. This descriptive study tries to determine the potential hazards that can be found in "crumb rubber" production process in PT Perkebunan Nusantara III (Persero) Kebun Gunung Para. We can see from the result that this process is divided into wet and dry processes. Potential hazards that found in "crumb rubber" production process are hearing loss, breathing disorders, slipped, hit by rubbers/raw materials, electric shock, hand grinded/severed/pinched, muscle disorders, hit by wheel barrow, hit by dryer box, stumbled by rail box and fire. Things that can be done to avoid these potential hazards are controlling and viewing attitude and manner in working, wear PPE instruments such as rubber boots, mask, ear muff, and gloves at work, installing Fire Extinguishers, clean the floors regularly, noticing the amount of raw materials that carried by workers, provide specialized trainings in machine operation, and perform machine maintenance regularly. Potential hazards in rubber producing process is fair high so installation of K3 warning signs, K3 promotion, and the use/availability of PPE needs to be increased.   Keywords : rubber processing, identification, potential hazard